Changes in the Bacterial Flora of Skin of Processed Broiler Chickens Washed in Solutions of Salicylic Acid - Hinton Jr., A.; Cason, J.A. (International Journal of Poultry Science, 2007)
Changes in the number of bacteria recovered from the skin of processed broilers after each of five consecutive washings in salicylic acid (SA) solutions was examined. Skin samples from commercially processed broiler carcasses were divided into 3 groups and washed in distilled water (control), 10% SA, or 20% SA by agitating skin in wash solutions in a Stomacher laboratory blender. After each wash, skin was transferred to fresh solutions and washing was repeated to provide samples washed 1 to 5 times in each solution. Washed skin was stomached in Butter field`s Phosphate Buffer to recover bacteria on the skin. Bacterial flora of the rinsates was enumerated on Plate Count (PC) Agar, Staphylococcus (STA) Agar, Levine Eosin Methylene Blue (EMB) Agar, Lactic Acid Bacteria (LAB) Agar, and Perfringens (PER) Agar with TSC supplement; and then bacterial isolates from each medium were identified. Results indicated that after each of 5 consecutive washes in water, there was no significant difference in the number of bacteria recovered from skin on any of the agar media. Significantly fewer bacteria were recovered on LAB Agar from skin after 5 washes in 10% SA than after 1 wash, but there was no significant decrease in the number of bacteria recovered on any other media after skin was washed in this solution. However, washing skin 4 or 5 times in 20% SA significantly reduced the number of bacteria recovered on PC and STA Agar, while no bacteria were recovered on EMB or LAB Agars from rinsates of skin washed 4 or 5 times in 20% SA or on PER Agar from skin washed 3 or more in the 20% solution. In vitro studies indicated that SA is bactericidal towards bacterial isolates recovered from skin and that resistance to the bactericidal activity of SA in descending order is Staphylococcus simulans > Lactobacillus > Escherichia coli > Clostridium perfringens. Findings indicate that successive washing of skin in SA may significantly reduce the number of bacteria recovered from the poultry skin and that the bactericidal activity SA can kill bacteria in vitro.